Application of numerical methods with MATLAB for modelling the AZT drug and the survival by AIDS - Rodríguez González, Ihosvany (2020)
In our work we conducted a study for solving differential equations an application to modeling in a particular case of the biopharmaceutical sector, which was necessary at the time realize the importance of the application of this drug in a disease that became a pandemic Worldwide. In this problem the impact of zidovudine (azidothymidine or AZT) described on the survival of those who develop acquired immunodeficiency syndrome (AIDS) infection with the Human Immunodeficiency Virus. For the solution of this model it is has an ordinary differential equation of first order with initial values on which the separation of variables is applied to obtain the real solution analytically and apply numerical methods 3 (Euler, Improved Euler and Runge Kuta 4) using MATLAB mathematical wizard to calculate approximate solutions. Finally, we show the results of the methods, the absolute and relative errors of each and a comparison with the analytical solution and their respective tables and graphs.